EVENT AS A TRANSFORMATION OF EVERYDAY LIFE MODUS OF SOCIAL BEING - Y. G. Boreiko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the study is to find out the interdependence of the event as a factor of transformations in the established areas of human life and everyday routine as a way of existence of social being, which cover various types of human activity. Theoretical basis of the research is based on understanding of everyday routine as a form of social reality, a complex and multidimensional object that is constantly evolving, includes new forms of reality, and is influenced by various social changes. The main function of everyday routine is the survival of individual and society, therefore the stable foundations of human existence play a dominant role in every life. In turn the event serves as a way of being existence, has a singular character, an individual expression, identifies elements that do not fit into the usual framework of everyday life. Originality of the obtained results lies in understanding event as the opposition of the phenomena world to the out of experience world of being, unexpected innovation that leads to the emergence of behaviours and structures that are new and unusual for everyday life. Event is not identical to empirical facticity, does not correspond to the usual understanding of phenomena and processes, and leads to a break from the everyday life, as it causes significant changes in human life on the individual and social levels. Unexpected change in everyday life caused by event is a traumatic collision with another dimension of being for an individual, as a result of it new meanings may open. Conclusions. On the background of everyday life, which is able to be in different states, function in a variety of relationships, to be manifested in numerous structures, junctions and connections, the event assumes the prospect of a new reality, contrary to previous representations. From existential point of view, event is always an interruption of everyday life, as for example, love or religious conversion. A large-scale event causes shocks that affect most or all individuals and communities that use multiple ways to react to an event – interpretation, selection, glorification, silence, valuations adjustment, phenomena, facts, celebration of holidays, rituals that are periodically repeated.